Behaviour of Steel I Beams with Web Openings - Jinan Laftah Abbas (Civil Engineering Journal, 2023)
This paper aims to study the behavior of steel I beams with web openings. However, web openings might lead to a noteworthy reduction in the load-carrying capacity of beams, but can also be so supportive and essential from an economic point of view. An experimental investigation and nonlinear three-dimensional finite element analysis using the ABAQUS computer program were planned and conducted on six steel I-beams having the same dimensions, different diameter ratio spacing, and opening shapes such as circular, rectangular, and hexagonal. Experimental results showed that the ultimate load of a steel beam with web openings reduced with an increase in the area of the opening. A circular opening has a stronger shape than a rectangular opening because a rectangle has fast deflection and torsion angles, so it resists an applied load less than a circular opening. Also, the beam with hexagonal openings is better than that with rectangular openings because hexagonal openings are more resistant to deflection and deformation than rectangular openings. The finite element results, which are validated against the experimental results, show good accuracy with the experiment. Besides, a parametric study is presented here to study the influence of varying the shape of openings on the value of the failure load and midspan deflection. It can be noticed that the steel beam with a circular opening, which had been tested experimentally and modeled by the Abaqus program, is the best case and gives a higher failure load as compared to the diamond, octagonal, trapezoidal, transverse, and longitudinal ellipses. Thus, providing web openings reduces the weight and increases structural efficiency. Doi: 10.28991/CEJ-2023-09-03-08 Full Text: PDF